Characterization of natural leaf senescence in tobacco (Nicotiana tabacum) plants grown in vitro - Uzelac, Branka; Janošević, Dušica; Simonović, Ana; Motyka, Václav; Dobrev, Petre I; Budimir, Snežana (Protoplasma, 2016)
Leaf senescence is a highly regulated final phase of leaf development preceding massive cell death. It results in the coordinated degradation of macromolecules and the subsequent nutrient relocation to other plant parts. Very little is still known about early stages of leaf senescence during normal leaf ontogeny that is not triggered by stress factors. This paper comprises an integrated study of natural leaf senescence in tobacco plants grown in vitro, using molecular, structural, and physiological information. We determined the time sequence of ultrastructural changes in mesophyll cells during leaf senescence, showing that the degradation of chloroplast ultrastructure fully correlated with changes in chlorophyll content. The earliest degenerative changes in chloroplast ultrastructure coinciding with early chromatin condensation were observed already in mature green leaves. A continuum of degradative changes in chloroplast ultrastructure, chromatin condensation and aggregation, along with progressive decrease in cytoplasm organization and electron density were observed in the course of mesophyll cells ageing. Although the total amounts of endogenous cytokinins gradually increased during leaf ontogenesis, the proportion of bioactive cytokinin forms, as well as their phosphate precursors, in total cytokinin content rapidly declined with ageing. Endogenous indole-3-acetic acid (IAA) levels were strongly reduced in senescent leaves, and a decreasing tendency was also observed for abscisic acid (ABA) levels. Senescence-associated tobacco cysteine proteases (CP, E.C. 3.4.22) CP1 and CP23 genes were induced in the initial phase of senescence. Genes encoding glutamate dehydrogenase (GDH, E.C. 1.4.1.2) and one isoform of cytosolic glutamine synthetase (GS1, E.C. 6.3.1.2) were induced in the late stage of senescence, while chloroplastic GS (GS2) gene showed a continuous decrease with leaf ageing.
Keywords: buněčná smrt; Cytokinins; cytokininy; Aging; chlorofyl; Leaf senescence; Plant Leaves; Metabolic Networks and Pathways; regulátory růstu rostlin; mezofylové buňky; Cellular Senescence; Mesophyll ultrastructure; rostlinné proteiny; Cell Death; stárnutí; tabák; Gene Expression; Tobacco; Plant Proteins; Mesophyll Cells; Chlorophyll; exprese genu; qRT-PCR; Plant Growth Regulators; metabolické sítě a dráhy; Nicotiana; listy rostlin; Phytohormones; stárnutí buněk